Effectiveness of Activity-Based Instruction (ABI) and Interactive Lecture Demonstration (ILD) in addressing misconceptions in geometric optics - PONTILLAS, SHERRYL (Archīum Ateneo, 2017)
This study compared the effectiveness of two methods under active learning, the Activity- based Instruction (ABI) and Interactive Lecture Demonstration (ILD), in correcting the misconceptions of the students in geometric optics. The respondents, which consisted of 62 science high school students, were divided into two groups. They were taught using ABI and ILD, separately. Their level of understanding before and after the intervention was assessed using the non-randomized pre-test post-test method. This study combined quantitative and qualitative analyses to assess the effectiveness of the two methods. Results revealed that both methods have successfully addressed the misconceptions held by the students, though statistics indicated that one method showed advantage over the other in correcting certain misconceptions. Based on the results of the study, recommendations to properly identify students' misconceptions, include it in the planning of the lesson and incorporate it in the discussion and in the assessment of learning, were suggested.